FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN: KECURANGAN AKUNTANSI PADA PT. BANK DKI - Swara, Silvia Permata; Saragih, Kuncu; Sinaga, Sautman (Universitas Kristen Indonesia, 2017)
This study was aimed at finding out whether there is a significant effect of internal control system, compensation, and information asymmetry on accounting fraud. This study was conducted at Bank DKI in Central Jakarta. This study belonged to quantitative research. The data source was primary data source. The data collection techniques used were questionnaire distributed. The respondents were group internal audit employees. The sampling technique used is purposive sampling. The data were analyzed using descriptive analysis, data quality testing, classical assumption testing, and multiple linear regression analysis using Statistical Package For Social Science (SPSS) 23. The results showed that (1) effective on internal control system has a significant positive effect on accounting fraud, (2) compensation does not a have a significant effect on accounting fraud, and (3) information asymmetry does not have a significant effect on accounting fraud.Key word : Effective on Internal Control System, Compensation, Information Asymetry, Accounting Fraud.